Down-regulation of the forkhead transcription factor Foxp1 is required for monocyte differentiation and macrophage function. - Shi, C; Sakuma, M; Mooroka, T; Liscoe, A; Gao, H; Croce, K; Sharma, A; Kaplan, D; Greaves, D; Wang, Y; Simon, D (2008)
Down-regulation of the forkhead transcription factor Foxp1 by integrin engagement controls monocyte differentiation in vitro. To determine whether Foxp1 plays a critical role in monocyte differentiation and macrophage functions in vivo, we generated transgenic mice (macFoxp1tg) overexpressing human FOXP1 in monocyte/macrophage lineage cells using the CD68 promoter. Circulating blood monocytes from macFoxp1tg mice have reduced expression of the receptor for macrophage colony-stimulating factor (c-Fms/M-CSFR), impaired migratory capacity, and diminished accumulation as splenic macrophages. Macrophage functions, including cytokine production, phagocytosis, and respiratory burst were globally impaired in macFoxp1tg compared with wild-type cells. Osteoclastogenesis and bone resorption activity were also attenuated in macFoxp1tg mice. In models of chemical and bacterial peritonitis, macFoxp1tg mice exhibited reduced macrophage accumulation, bacterial clearance, and survival. Enforced overexpression of c-Fms/M-CSFR reversed the cytokine production and phagocytosis defects in macFoxp1tg macrophages, indicating that repression of c-fms/M-CSFR is likely the dominant mechanism responsible for Foxp1 action in monocyte differentiation and macrophage function. Taken together, these observations identify down-regulation of Foxp1 as critical for monocyte differentiation and macrophage functions in vivo.